2014
DOI: 10.7314/apjcp.2014.15.13.5449
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of TP53 but not K-ras Gene Mutations in Bolivian Patients with Gallbladder Cancer

Abstract: Although genetic characteristics are considered to be a factor influencing the geographic variation in the prevalence of gallbladder cancer (GBC), they have not been well studied in Bolivia, which has a high prevalence rate of GBC. The purpose of this study was to examine the frequency of TP53 and K-ras mutations in Bolivian patients with GBC and to compare them with our previous data obtained in other high-GBC-prevalence countries, namely Japan, Chile, and Hungary. DNA was extracted from cancer sites in paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
4
18
0
4
Order By: Relevance
“…Metaplasia most commonly arises due to inflammation caused by chronic gallstone irritation [14]. Inflammation then leads to increased expression of COX2 and inhibition of tumor suppressor genes such as p53 [14, 17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Metaplasia most commonly arises due to inflammation caused by chronic gallstone irritation [14]. Inflammation then leads to increased expression of COX2 and inhibition of tumor suppressor genes such as p53 [14, 17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…In this present study we did not found any mutation of codon 13 and 61 may be due to stage of disease as our sample consist of only stage II. Null association studies with K-RAS mutation were also reported by Mohammad et al (2013) Chronic Myloid Leukemia, Takao Asai et al (2014) in Gall bladder cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Cardesa et al (11) represented that TP53 gene mutations were observed in up to 50% of head and neck squamous-cell carcinomas and approximately 65% of them have aberrant expression of TP53. Szymańska et al (12) also reported that TP53 was the most frequently mutated gene in human cancer, such as hepatocellular carcinoma and oesophagus (13), exploredTP53 mutations in GBC patients, and found nearly half of GBC patients have TP53 mutations. In our meta-analysis, we also found that TP53 was the most recurrent mutated gene in GBC (crude P value =1.44×10 -6 , corrected P value =1.00×10 -3 , Table 2).…”
Section: Meta-signature Of Mutated Genes In Gbcmentioning
confidence: 98%